Psychological Explanation of Masochism in Ghalib’s Poetry - Iqbal, Sajid; Abbas Kazmi, Kamran (sourcecoder, 2022)
Naeem Al-Hamid is a well-known poet in Saudi Arabia. But in the Masochism is a psychological term used to describe people who take pleasure in suffering and pain. Basically the roots of this perversion are connected with the human sex life. Mosochism is related to death instinct. This instinct tries to push the organism towards an inorganice state. In Ghalib’s poetry, masochism exists in a colourul style. At its core is the dominant atmosphere, mood, trauma of personal life and the story of the up heaval of collective life. In Ghalib’s poetry, there is a large handful of feelings of inferiority, superiority, egoism, fear, jealously, delusion, despair and depression in the background of the psychology of masochism.